A Contemporary Study on Quantum-Computing Security Mechanisms in 5G Networks - et. al., Rydhm Beri , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
5G communication technology works with the integration of several technologies viz. Cloud Computing, network partitioning and software based networks. This integration allows the communication between thousands of device across the world which have enormous issues related to data protection, data authenticity, and data confidentiality. So, there is an immense need of secure protocols to face or resolve security related issues related to design and operation of 5G network. Moreover, some structured cryptography protocols required to develop and accomplish data security in 5G communication. The study focussing on the comprehensive consequences of quantum computing on security implementations of 5G mobile communications. The study discussing about the cryptographic algorithm used in 5G, and what are the various consequences of involvement of quantum computing.